Outcomes after viral load rebound on first-line antiretroviral treatment in children with HIV in the UK and Ireland: an observational cohort study. Issue 4 (April 2015) - Childs, Tristan; Shingadia, Delane; Goodall, Ruth; Doerholt, Katja; Lyall, Hermione; Duong, Trinh; Judd, Ali; Gibb, Di M; Collins, Intira Jeannie; ,
Summary: Background: About a third of children with HIV have virological failure within 2 years of beginning antiretroviral treatment (ART). We assessed the probability of switch to second-line ART or virological re-suppression without switch in children who had virological rebound on first-line ART in the UK and Ireland. Methods: In this study, we used data reported to the Collaborative HIV Paediatric Study (CHIPS), a national multicentre observational cohort. We included children with virological rebound (confirmed viral load >400 copies per mL after suppression <400 copies per mL) on first-line ART. We did a competing-risk analysis to estimate the probability of switch to second-line treatment, confirmed resuppression (two consecutive viral load measurments <400 copies per mL) without switch, and continued viral load above 400 copies per mL without switch. We also assessed factors that predicted a faster time to switch. Findings: Of the 900 children starting first-line ART who had a viral load below 400 copies per mL within a year of starting treatment, 170 (19%) had virological rebound by a median of 20·6 months (IQR 9·7–40·5). At rebound, median age was 10·6 years (5·6–13·4), median viral load was 3·6 log10 copies per mL (3·1–4·2), and median CD4% was 24% (17–32). 89 patients (52%) switched to second-line ART at a median of 4·9 months (1·7–13·4) after virological rebound, 53 (31%) resuppressed without switch (19 [61%] of 31 patients on a first-line regimen that included a protease inhibitor and 31 [24%] of 127 patients on a first-line regimen that included a non-nucleoside reverse transcriptase inhibitor; NNRTI), and 28 (16%) neither resuppressed nor switched. At 12 months after rebound, the estimated probability of switch was 38% (95% CI 30–45) and of resuppression was 27% (21–34). Faster time to switch was associated with a higher viral load (p<0·0001), later calendar year at virological rebound (p=0·02), and being on an NNRTI-based or triple nucleoside reverse transcriptase inhibitor-based versus protease-inhibitor-based first-line regimen (p=0·001). Interpretation: A third of children with virological rebound resuppressed without switch. Clinicians should consider the possibility of resuppression with adherence support before switching treatment in children with HIV. Funding: NHS England (London Specialised Commissioning Group).